Design and development of primers for detection of Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis - Azimi, Leila; Shirkavand, Fatemeh; Armin, Shahnaz; Karbasian, Fereshteh; Khodaei, Hannan (GMS Hygiene and Infection Control)
Background: The mortality rate of meningitis is still alarmingly high in certain regions across the globe. The objective of this research is to identify the most effective primers for detecting Streptococcus (S.) pneumoniae, Haemophilus (H.) influenzae, and Neisseria (N.) meningitidis using Real-Time PCR technology. Materials and methods: Two sets of primers were developed for detecting S. pneumoniae, H. influenzae, and N. meningitidis using the Primer Biosoft Allele ID 7.6 application. The study examined the minimum bacterial copy numbers detectable by each primer, as well as their specificity. Results: CtrA and hpd2 could detect the 400 copy numbers/ml of H. influenzae, and N. meningitidis and LytA2 could detect the 40 copy numbers/ml of S. pneumoniae. The sensitivity and specificity of all primers was 100% (CI: 95%). Conclusion: Using more sensitive primers to detect the bacterial agent responsible for causing bacterial meningitis increases the chance of identifying the causative bacteria. The primers designed in this study could identify the selected bacteria with at least 10 times more sensitivity than the currently available commercial diagnostic kits in Iran.